"I think it's communication and trust and sharing everything": Qualitative evidence for a model of healthy intimate relationships in Black women living with HIV and men in KwaZulu‐Natal, South Africa. Issue 4 (21st December 2021) - Belus, Jennifer M.; Bradley, Valerie D.; van Heerden, Alastair; Msimango, Lindani I.; Barnabas, Ruanne V.; van Rooyen, Heidi
Abstract: In South Africa, couple‐based interventions (CBIs) have been used to increase HIV testing, reduce HIV transmission, and shift relationship dynamics. To understand local definitions of healthy relationships, this study sought to collect qualitative data on a model of healthy relationships in a semi‐rural area of KwaZulu‐Natal, South Africa. We conducted semi‐structured qualitative interviews with HIV‐positive women ( n  = 15) and men of mixed HIV status ( n  = 15) who were in heterosexual, monogamous relationships (not with each other). Thematic analyses guided coding. Three primary healthy relationship behaviour themes emerged, labelled open communication, couple‐level problem‐solving, and active relationship building, which were related to various relationship facets (trust, support, respect, commitment, and connection). We purposively explored contextual themes, namely the role of HIV, positive community involvement, and power dynamics, to better situate the healthy relationship behaviour themes. HIV was not central to relationship conceptualisations and three different power structures (shared power/flexible gender norms, shared power/traditional gender norms, male‐dominated power/traditional gender norms) were described as being healthy. This model of healthy relationships is similar to observed definitions in other African countries and in high‐income settings. Findings can inform HIV programming content for couples in KwaZulu‐Natal, particularly the active relationship building component. Resumen: En Sudáfrica, se han utilizado intervenciones basadas en la pareja para aumentar las pruebas de detección de VIH, disminuir la transmisión del VIH y cambiar la dinámica de las relaciones. Para comprender las definiciones locales de relaciones saludables, en el presente estudio se procuró recoger datos cualitativos sobre un modelo de relaciones saludables en un área semirrural de KwaZulu‐Natal, Sudáfrica. Realizamos entrevistas cualitativas semiestructuradas con mujeres VIH positivo (n= 15) y hombres de estados variados en relación con el VIH (n = 15) que estaban en relaciones heterosexuales y monógamas (no entre ellos). Los análisis temáticos guiaron la codificación. Surgieron tres temas principales de conducta en las relaciones saludables: comunicación abierta marcada, resolución de problemas a nivel de la pareja, y construcción activa de la relación, que estuvieron relacionados con varios aspectos de las relaciones (la confianza, el apoyo, el respeto, el compromiso y la conexión). Analizamos específicamente temas contextuales, por ejemplo, el papel del VIH, la participación positiva en la comunidad y la dinámica de poder para ubicar mejor los temas de conducta en las relaciones saludables. El VIH no fue fundamental para las conceptualizaciones de las relaciones y se describieron como saludables tres estructuras de poder diferentes (poder compartido/normas flexibles de género, poder compartido/normas tradicionales de género, poder predominantemente masculino/normas tradicionales de género). Este modelo de relaciones saludables es similar a las definiciones observadas en otros países africanos y en ámbitos de ingresos altos. Los resultados pueden orientar el contenido de los programas sobre el VIH para parejas en KwaZulu‐Natal, particularmente el componente de construcción activa de la relación. 摘要: 在南非, 基于伴侣的干预措施 (CBI) 被用来增加HIV艾滋病毒检测, 减少HIV艾滋病毒传播, 并改变关系动态。为了了解当地对健康关系的定义, 本研究试图在南非夸祖鲁‐纳塔尔省的一个半农村地区收集关于健康关系模式的定性数据。我们对HIV阳性的女性 (n = 15) 和混合HIV状态的男性 (n = 15) 进行了半结构化的定性访谈, 他们处于异性恋、一夫一妻制的关系中 (彼此之间没有关系) 。本研究采用主题分析来指导了编码工作, 归纳出以下三个主要的健康关系行为主题, 分别是: 开放性沟通、伴侣层面的问题解决和积极的关系建立, 它们与各种关系的各个方面 (信任、支持、尊重、承诺和联系) 有关。我们有目的地探索了背景主题, 即HIV的作用、积极的社区参与和权力动态, 以更好地定位健康关系行为主题。HIV不是关系概念化的核心, 三种不同的权力结构 (共享权力/灵活的性别规范, 共享权力/传统的性别规范, 男性主导的权力/传统的性别规范) 被描述为是健康的。这种健康关系的模式与在其他非洲国家和高收入环境中观察到的定义相似。研究结果可以为夸祖鲁‐纳塔尔省伴侣的HIV计划内容提供参考, 特别是促进建立积极的关系的那一模块。